INTRODUCING THE CARD EDITING APPLICATION OF THE LIMSTROM DIDACTIC GAME - Szilágyi, Szilvia; Korei, Attila; Torok, Zsuzsanna; Vaičiulytė, Ingrida (PROFESSIONAL STUDIES: Theory And Practice, 2023)
Game-based learning plays an important role in all education and learning processes, including higher education nowadays. In the course, Mathematical Analysis, offered during the first semester, all students studying informatics learn about sequences of real numbers, convergence, and limits. These concepts are of key importance to understand advanced mathematical concepts and successfully complete advanced courses. Based on the benefits of game-based learning we came up with the idea of LimStorm that helps study groups of 4-10 students to learn and practice the limits of sequences of real numbers. In our paper we introduce a self-developed application which is suitable for generating decks of mathematical didactic card games, for example the deck of LimStorm.